Interleukin - 12 p35 encoding gene of cattle and sheep harbours a polymorphic T stretch in intron 4 - Schmidt, P.; Kuhn, C.; Kang'a, S.; Hanotte, Olivier H.; Vanselow, J.; Anton, I.; Langner, Ch; Schwerin, M. (Wiley, 2000)
The paper first describes interleukin-12 P35 encoding gene and discusses its role. It then looks into PCR conditions and sequencing; genotyping; sequencing; polymorphism frequency; mendelian inheritance; chromosomal location in sheep and cattle of different species.